TRAGEDI DI BALIK DINDING RUMAH: DINAMIKA PSIKOLOGIS DAN KRIMINOLOGI PADA KASUS PEMBUNUHAN BERENCANA DALAM BUDAYA PATRIARKI - Syukriyya uns (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
This study discusses the phenomenon of domestic violence with a focus on cases of premeditated murder between husband and wife from a psychological and criminological perspective. This type of descriptive qualitative research uses a case study approach. The cases used are sadistic murders by husbands against wives and vice versa, which are caused by economic factors, interpersonal conflicts, emotional stress and schizophrenic conditions which give rise to aggressive attitudes. The involvement of gender in a patriarchal context is also debated in the dynamics of this crime. The results of this study underscore the importance of improvements in gender equality and understanding the psychological dynamics underlying cases of domestic homicide. Keywords: emotional; gender; domestic violence; patriarchy; premeditated murder